2016
DOI: 10.4238/gmr.15017725
|View full text |Cite
|
Sign up to set email alerts
|

Bovine dopamine receptors DRD1, DRD4, and DRD5: genetic polymorphisms and diversities among ten cattle breeds

Abstract: ABSTRACT. The aim of this study was to analyze the allelic frequency distribution and segregation among breeds and/or between different cattle genetic groups of four novel single nucleotide polymorphisms of the bovine DRD1 and DRD5 genes and one reported SNP from the DRD4 gene. One hundred and nine-animals from ten different cattle breeds were genotyped and allelic frequencies for each locus were estimated. There were significant differences in the allelic frequencies (P < 0.05) among breeds for the DRD1 and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Some of them were already related to sperm functionality and oocyte quality in bovines (Angulo et al, 2015; Selvaraju et al, 2018) and embryo implantation in mice (Ai et al, 2016). Additional genes previously related to differences in aggressiveness and temperament ( Dopamine receptor D 5, DRD5 , [Sifuentes‐Rincon et al, 2016]), heat stress tolerance ( DNAJ heat shock protein family member C12 , DNAJC12 , [Dai et al, 2018]) and muscle growth ( Leucine Rich Repeat Containing 20 , LRRC20 , [Bazile et al, 2020]) in cattle were found among the ROHi produced very recently. Despite they have not been described as candidate genes in goats, all of them are related to productive traits of interest in the Florida goat, which are characterized as fertile, calm and resilient to thermal increase.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them were already related to sperm functionality and oocyte quality in bovines (Angulo et al, 2015; Selvaraju et al, 2018) and embryo implantation in mice (Ai et al, 2016). Additional genes previously related to differences in aggressiveness and temperament ( Dopamine receptor D 5, DRD5 , [Sifuentes‐Rincon et al, 2016]), heat stress tolerance ( DNAJ heat shock protein family member C12 , DNAJC12 , [Dai et al, 2018]) and muscle growth ( Leucine Rich Repeat Containing 20 , LRRC20 , [Bazile et al, 2020]) in cattle were found among the ROHi produced very recently. Despite they have not been described as candidate genes in goats, all of them are related to productive traits of interest in the Florida goat, which are characterized as fertile, calm and resilient to thermal increase.…”
Section: Discussionmentioning
confidence: 99%
“…Lourenco-Jaramillo et al [185] re-sequenced the DBH gene and identified significant haplotype differences between Brahman and HF cattle, which might be a result of differences in temperament between the two breeds. Similarly, Sifuentes-Rincón et al [186] found differences in genetic polymorphisms in different dopamine receptor genes between Bos taurus and Bos indicus breeds, which might be due to breed differences in aggressiveness and temperament. Dopamine, serotonin, and oxytocin pathways are mainly involved in the genetic mechanisms of mammalian maternal behaviour [187].…”
Section: Genetics and Genomics Of Biomarkers As Indicators For Cattle...mentioning
confidence: 92%
“…Temperament in cattle is an important trait observed as a response to handling and human-facing activities [1]. There is a growing list of candidate genes associated with temperament traits [2,3], and their complex genetic architecture still needs to be elucidated. Most genetic variations in candidate genes for temperament are based on Single Nucleotide Polymorphisms (SNPs).…”
Section: Introductionmentioning
confidence: 99%